2021
DOI: 10.1002/mgg3.1831
|View full text |Cite
|
Sign up to set email alerts
|

Filling the gap: A thorough investigation for the genetic diagnosis of unsolved polyposis patients with monoallelic MUTYH pathogenic variants

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Mammalian MutY homologue (MUTYH) encodes a DNA glycosylase involved in base excision repair during DNA replication and damage repair. PVs/LPVs in MUTYH are associated with autosomal recessive colorectal adenomatous polyposis, but interestingly, monoallelic variants on this gene have been reported by both our and other groups as being associated with cancer predisposition in several patients [30,31]. An interesting case in the present study is represented by the detection of a MUTYH c.734G>A variant in one female patient with a personal history of breast cancer diagnosed at the age of 44 years, previously tested for BRCA1/2 variants at another institute and found to be negative.…”
Section: Discussionmentioning
confidence: 72%
“…Mammalian MutY homologue (MUTYH) encodes a DNA glycosylase involved in base excision repair during DNA replication and damage repair. PVs/LPVs in MUTYH are associated with autosomal recessive colorectal adenomatous polyposis, but interestingly, monoallelic variants on this gene have been reported by both our and other groups as being associated with cancer predisposition in several patients [30,31]. An interesting case in the present study is represented by the detection of a MUTYH c.734G>A variant in one female patient with a personal history of breast cancer diagnosed at the age of 44 years, previously tested for BRCA1/2 variants at another institute and found to be negative.…”
Section: Discussionmentioning
confidence: 72%
“…Interestingly, our study showed that 94% of MUTYH carriers had a heterozygous variant. PVs/LPVs in MUTYH are associated with colorectal adenomatous polyposis autosomal recessive, while recent literature data revealed the association between monoallelic MUTYH variants and several type of cancer (Dell'Elice et al, 2021). BC, PC and OC, together with colon and prostate cancer, are the major tumors linked to clinical familiar history, as well as the major BRCA-associated cancers (Daly et al, 2021).…”
Section: Discussionmentioning
confidence: 99%